Strategi Amerika Serikat melalui Program KL-YES (Kennedy Lugar-Youth Exchange And Study) dalam Upaya Memperbaiki Citra Negara: Studi Kasus Indonesia - Auliaur Rahman, Maulana Ammar; Rosyidin, Mohamad (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Global War on Terror Policy by the United States became the first step in the emergence of negative view of the United States and matters relating to it by the Muslim community, especially Indonesia. The rise of negative views on the United States, or what is commonly referred to as Anti-Americanism, is because they are considered to involve to the rise of terrorism movements in the name of religion so that many muslim receive discriminatory treatment. To improve relations with the Islamic world, the United States Government decided to create the KL-YES program with the aim of creating mutual understanding with the Islamic world. The purpose of this study itself is to describe the efforts made by the KL-YES program in order to create mutual understanding between Muslim communities and the American community. By using Soft Power Currencies concept from Alexander Vuving,this study is try to see how the KL-YES program is able to create interest in the targets to represent the goals to be achieved, which in this case improve the image of the United States in Indonesia. By using descriptive research type, using primary and secondary data, and using qualitative data analysis, this study shows that the KL-YES program is able to create a positive image of the participants through three variables, namely Benignty, Brilliance, and Beauty.